Large-Area, Free-Standing, Two-Dimensional Supramolecular Polymer Single-Layer Sheets for Highly Efficient Electrocatalytic Hydrogen Evolution - Dong, Renhao; Pfeffermann, Martin; Liang, Haiwei; Zheng, Zhikun; Zhu, Xiang; Zhang, Jian; Feng, Xinliang (Angewandte Chemie International Edition, 2015)
The rational construction of covalent or noncovalent organic two-dimensional nanosheets is a fascinating target because of their promising applications in electronics, membrane technology, catalysis, sensing, and energy technologies. Herein, a large-area (square millimeters) and free-standing 2D supramolecular polymer (2DSP) single-layer sheet (0.7-0.9 nm in thickness), comprising triphenylene-fused nickel bis(dithiolene) complexes has been readily prepared by using the Langmuir-Blodgett method. Such 2DSPs exhibit excellent electrocatalytic activities for hydrogen generation from water with a Tafel slope of 80.5 mV decade-1 and an overpotential of 333 mV at 10 mA cm-2, which are superior to that of recently reported carbon nanotube supported molecular catalysts and heteroatom-doped graphene catalysts. This work is promising for the development of novel free-standing organic 2D materials for energy technologies.
CRIS-Team Scopus Importer:2023-03-20
Keywords: electrocatalysis; hydrogen evolution reaction; nanostructures; polymers; supramolecular chemistry